The coat protein of citrus yellow vein clearing virus directly targets the ascorbate peroxidase 1 in lemon (ClAPX1) to facilitate virus accumulation - Wang, Chunqing; Zhang, Qi; Li, Jiaxin; Wang, Xinliang; Li, Chuxin; Bin, Yu; Song, Zhen (Frontiers in Plant Science, 2023)
Reactive oxygen species (ROS) are closely related to the antiviral immune response of plants, while virus can regulate ROS through various pathways to facilitate their own infection or replication.Citrus yellow vein clearing virus (CYVCV) is one of the most devastating viruses affecting lemon (Citrus limon) industry worldwide. However, the pathogenesis of CYVCV remains poorly understood.In this study, direct interaction between the coat protein (CP) of CYVCV and the ascorbate peroxidase 1 of lemon (ClAPX1) was confirmed for the first time by yeast two-hybrid, Bimolecular Fluorescence Complementation, and Co-immunoprecipitation assays. Transient expression of CP in lemon and Nicotiana benthamiana significantly enhanced the enzyme activity of the ClAPX1, and then inhibited the accumulation of H2O2. In addition, overexpression of ClAPX1 in lemon by transgene significantly promoted CYVCV accumulation and depressed the expression of most genes involved in jasmonic acid (JA) signaling pathway. Correspondingly, ClAPX1 silencing by RNA interference inhibited CYVCV accumulation and increased the expression of most genes involved in JA signaling pathway.To our knowledge, this is the first report that viruses regulate ROS by targeting APX directly, thereby suppressing host immune response and promoting viral accumulation, which may be mediated by JA signaling pathway.